Constitution of Republic of Uzbekistan (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation: This article is about the Constitution of the Republic of Uzbekistan. The constitution, which is a symbol of the nation, was created by whom and when, the law, substances and clauses are discussed.